If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(5)(g) + 5(3) + 25 = 115 Multiply 5 * 5 25g + 5(3) + 25 = 115 Multiply 5 * 3 25g + 15 + 25 = 115 Reorder the terms: 15 + 25 + 25g = 115 Combine like terms: 15 + 25 = 40 40 + 25g = 115 Solving 40 + 25g = 115 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 25g = 115 + -40 Combine like terms: 40 + -40 = 0 0 + 25g = 115 + -40 25g = 115 + -40 Combine like terms: 115 + -40 = 75 25g = 75 Divide each side by '25'. g = 3 Simplifying g = 3
| 7(3+4x)=21 | | 4x-44=4(5x+1) | | 3(c-8)=c+76 | | 3x-2(x-3)=4-(5x-1) | | 47.90=0.045k+6.5 | | 6-6x=6x-10x-6 | | 6+x=4.25 | | 3.14159265359=7x-2y | | 2h^2-2h-1=0 | | 2(6-x)=8 | | -3x-82=8x+50 | | 10r-9=54 | | 3(3x-2)=5x-30 | | 3(k-50)-k=2k+84 | | 2d+97=-d-17 | | -3z-8(2z+y)= | | -57+5x=-x+45 | | 49-k=19 | | 2x-5(x-3)=-4+2x-6 | | -4x^2-6x=192 | | 90=n+n-3 | | 4(2a+30)=5(a+144) | | -7x-19=51 | | 90=x+20+x | | -4(y+2)=-9y+2 | | 8(t-2)+7t=5(3t+3)-9 | | 2(2.5-9)+6b=14 | | 2(4x+3)-2x=4+3x | | 5x-4(-1x-3)=8 | | 1.00x+100=2.50x | | 4x+17+4x-39=90 | | 2b+3(b-2)=9 |